Physicochemical and sensory analyses of high fibre bread incorporated with corncob powder - Lee, Choon Min; Gan, Yee Lin; Chan, Yong Lin; Yap, Kwai Ling; Tang, Teck Kim; Tan, Chin Ping; Lai, Oi Ming (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The primary objectives of the present work were to produce corncob powder (CCP) from corncobs and incorporate the CCP into bread formulation in order to develop high fibre bread, and to investigate the physicochemical and sensory properties of the produced high fibre bread (HFB). The corncobs were collected and washed before they underwent the grinding and drying processes. The obtained CCP was incorporated into the bread formulation in three different proportions (5, 10 and 20%) to partially substitute bread flour in the formulation. All three bread samples and the control (0% CCP in the formulation) were analysed to obtain their physicochemical and sensory properties. The incorporation of CCP significantly affected the texture, colour and volume attributes of the produced breads. Increasing the content of CCP in the formulation was found to be responsible for firmer, smaller and darker bread loaves as compared to the composite bread samples. The bread formulation incorporated with 10% CCP had the highest mean scores (7.00) of overall acceptability among all the other formulations, and it was comparable to the commercial breads in the current market.